potencias

Escribe como potencia única:

- a)  3^{-2} \cdot 3 \cdot 3^4
- b)  \frac{2^{-3} \cdot 10^3}{5^3 \cdot 2^2 \cdot 3^{-2}}

SOLUCIÓN

- a)  3^{-2} \cdot 3 \cdot 3^4 = 3^3

- b)  \frac{2^{-3} \cdot 10^3}{5^3 \cdot 2^2 \cdot 3^{-2}}  =
 \frac{2^{-3} \cdot (2 \cdot 5)^3}{5^3 \cdot 2^2 \cdot 3^{-2}}  =
 \frac{2^{-3} \cdot 2^3 \cdot 5^3}{5^3 \cdot 2^2 \cdot 3^{-2}}  =
 \frac{2^0 \cdot \cancel{5^3}}{\cancel{5^3} \cdot 2^2 \cdot 3^{-2}}  =\frac{1}{2^2 \cdot 3^{-2}} = \frac{3^2}{2^2} = \left( \frac{3}{2} \right)^2